Alternative Perspectives on Peacebuilding Theories and Case Studies - Cogan, Mark S.; Sakai, Hidekazu (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book analyses and furthers the academic debates on post-liberal peacebuilding, through a number of conceptual, theoretical and empirical research outputs. Part I includes a review of how the recent discourse on peacebuilding has evolved, and three conceptual/theoretical perspectives relevant to post-liberal peacebuilding. In particular, the editors propose the concept of bespoke peacebuilding to articulate key features of new peacebuilding models. Part II introduces five case studies that present how alternative peacebuilding models are being shaped (or can be shaped) in practice. Essential reading for scholars and students in Peace and Conflict Studies, International Relations, and International Security Studies. Chapter 8 is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. Mark S. Cogan is Associate Professor of Peace and Conflict Studies at Kansai Gaidai University, Japan. He is a former communications specialist with the United Nations, serving in Southeast Asia, Sub-Saharan Africa and the Middle East. His research interests are vast, including security studies, peacebuilding, human rights, and the broader Indo-Pacific region. In addition to his research, he has published more than 120 commentaries and policy papers in major newspapers and think tanks, including the Observer Research Foundation (ORF), Bangkok Post, South China Morning Post, Southeast Asia Globe, the Diplomat Magazine, Geopolitical Monitor, Pacific Forum and more. Hidekazu Sakai is Professor at Kansai Gaidai University, Japan. His research interests include international relations theory, international security, peacebuilding, and Indo-Pacific politics. His publications include Re-rising Japan: Its Strategic Power in International Relations (New York: Peter Lang, 2017), co-edited with Yoichiro Sato, and The US-Japan Security Community: Theoretical Understanding of Transpacific Relationships (London: Routledge, 2018).
1. Introduction: Toward Bespoke Peacebuilding -- 2. Conceptualizing Bespoke Peacebuilding -- 3. "Peaces of the Puzzle": Mapping the Trajectories of Three Decades of Peacebuilding Scholarship -- 4. Bespoke Peacebuilding Through an International Quasi Leviathan: Bridging Basic Human Needs (BHNs) and Power -- 5. Violent Non-State Actors and Trust Building -- 6. A Holistic Peace: Buddhism and Liberal Peace -- 7. Contributions to Peacekeeping for Promotion of Localized Rwandan Norms -- 8. Controlling Violence by the Dominant Coalition: A Comparative Study of the Philippines (Mindanao) and Myanmar -- 9. Mediation as Peacebuilding: Faith-Based Mediators in Lesotho's Peacebuilding Process -- 10. The Lack of Trust in Failed Statebuilding: The Case of the Disarmament, Demobilization, and Reintegration (DDR) in Afghanistan -- 11. Conclusion.
Keywords: Peace; Security, International; Globalization; Peace and Conflict Studies; International Security Studies; Globalization